2012
DOI: 10.1051/0004-6361/201219336
|View full text |Cite
|
Sign up to set email alerts
|

DoAr 33: a good candidate for revealing dust growth and settling in protoplanetary disks

Abstract: Aims. We aim to evaluate the evolutionary stage of the circumstellar disk around DoAr 33, a T Tauri star in the Ophiuchus molecular cloud and a promising target for follow-up observations to find signs of dust evolution in protoplanetary disks. Methods. The currently available data on DoAr 33 comprises its spectral energy distribution from the optical to the millimeter regimes. This data set allows us to characterize the structure of a circumstellar disk using self-consistent radiative transfer models. We empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 60 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…For the star and disk parameters, we use a model which has been applied to explain various spatially-resolved multi-band observations of protostellar disks (Wolf et al 2003Schegerer et al 2008Schegerer et al , 2009Sauter et al 2009;Madlener et al 2012;Liu et al 2012;Gräfe et al 2013). The model uses parameters of a typical T Tauri system.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…For the star and disk parameters, we use a model which has been applied to explain various spatially-resolved multi-band observations of protostellar disks (Wolf et al 2003Schegerer et al 2008Schegerer et al , 2009Sauter et al 2009;Madlener et al 2012;Liu et al 2012;Gräfe et al 2013). The model uses parameters of a typical T Tauri system.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…A way to improve the prediction is to modify the underlying dust distribution. In particular a spatial variation of the particle size, caused by dust settling and segregation of large dust particles, has a strong influence on the local chromaticity and thus on scattered and reemitted radiation from the disk (e. g., Pinte et al 2008;Liu et al 2012;Gräfe et al 2013). Figure 9 shows the calculated temperature in the disk's midplane for the best-fit model.…”
Section: Simulated Maps and Radial Profilesmentioning
confidence: 99%
“…If CEN 34 is an evolved star the circumstellar envelope is a more plausible assumption than a circumstellar disk (Fujii et al 2002). We used the simulated annealing approach described in Liu et al (2012) to model the observed SED and to estimate the mass of circumstellar material. We explored the scenario of a spherical envelope that is commonly adopted to mimic the dust shell surrounding a post-AGB star.…”
Section: Extinction and Luminositymentioning
confidence: 99%